Selection of Rhizobium strains for forest legumes - Faria, Sergio Miana de; Moreira, V. C.G.; Franco, Avilio A. (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this study was to evaluate different strains of Rhizobium in sterile pots for the following forest species: Mimosa caesapiniaefolia Benth, Mimosa scabrella Benth, Dimorpandra exaltata Schott, Albizia falcataria (L.) Bacher, Bowdichia virgilioides HBK and Dalbergia nigra Fr. Allem and test the nodules using the acetylene reduction assay before the isolation of Rhizobium. An experiment was also performed to select strains for Mimosa scabrella Benth, using pots with soil. For all the species studied efficient Rhizobium strains were found, which gave well nodulated plants and good development of the aerial tissue. Isolation of Rhizobium from the most active nodules as selected by the acetylene reduction assay of individual nodules produced the most efficient strains.
Keywords: simbiosis; N2 fixation